Penanganan Permukiman Kumuh di Kelurahan Kota Uneng Kabupaten Sikka - Marsi Nini Aryanti; Yosefina Andia Dekrita; Margaretha Yulianti (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2024)
This study aims to find out the role of the Regional Research and Innovation Development Planning Agency in Handling Slum Settlements in Uneng City Subdistrict, Sikka Regency. The problems faced are limited basic infrastructure such as roads, clean water and inadequate sanitation. This is because this area has experienced a significant increase in population and this has not been balanced with the development of adequate basic infrastructure. The research method used is a qualitative method and is analyzed qualitatively. The results of this research show that the role of the Regional Research and Innovation Development Planning Agency in Handling Slum Settlements in Uneng City Subdistrict is to coordinate aspects of the preparation and integration of policies, strategies, norms, standards, guidelines and criteria for the implementation of Housing and Settlement Areas (PKP), Coordinating technical aspects of defense, licensing, design and technical feasibility as well as integration of Housing and Settlement Area (PKP) facilities and infrastructure, Coordinating institutional aspects, including coordinating, formulating policies, strengthening institutional capacity, as well as building partnerships with other parties including the community in the form of empowerment and cooperation as well as developing databases and information on housing and residential areas (PKP), Coordinating and developing a monitoring and evaluation system for PKP implementation, including performance measurement and PKP standard parameters.